2007
DOI: 10.1084/jem.20070876
|View full text |Cite
|
Sign up to set email alerts
|

FBW7 mutations in leukemic cells mediate NOTCH pathway activation and resistance to γ-secretase inhibitors

Abstract: γ-secretase inhibitors (GSIs) can block NOTCH receptor signaling in vitro and therefore offer an attractive targeted therapy for tumors dependent on deregulated NOTCH activity. To clarify the basis for GSI resistance in T cell acute lymphoblastic leukemia (T-ALL), we studied T-ALL cell lines with constitutive expression of the NOTCH intracellular domain (NICD), but that lacked C-terminal truncating mutations in NOTCH1. Each of the seven cell lines examined and 7 of 81 (8.6%) primary T-ALL samples harbored eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
592
3
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 617 publications
(636 citation statements)
references
References 55 publications
37
592
3
4
Order By: Relevance
“…Although the status of the Notch locus was not examined in tumors from these mice, evidence from human T-ALL samples gives insight into the Fbw7-Notch dynamic in leukemogenesis. Inactivating mutations of Fbw7 were found in 30% of human T-ALL samples examined, and analysis of these tumors revealed that only wild-type or HD mutant Notch forms were expressed (O'Neil et al, 2007;Matsuoka et al, 2008). Whereas, Notch PEST domain mutations were only found in samples expressing wild-type Fbw7, these data imply that in T-ALL, an inactivating Fbw7 mutation would have the same effect as N ICD PEST mutations, increasing Notch activity by decreasing Notch degradation by the proteosome.…”
Section: Fbw7 Regulates Notch Stability and Is Mutated In T-allmentioning
confidence: 68%
See 1 more Smart Citation
“…Although the status of the Notch locus was not examined in tumors from these mice, evidence from human T-ALL samples gives insight into the Fbw7-Notch dynamic in leukemogenesis. Inactivating mutations of Fbw7 were found in 30% of human T-ALL samples examined, and analysis of these tumors revealed that only wild-type or HD mutant Notch forms were expressed (O'Neil et al, 2007;Matsuoka et al, 2008). Whereas, Notch PEST domain mutations were only found in samples expressing wild-type Fbw7, these data imply that in T-ALL, an inactivating Fbw7 mutation would have the same effect as N ICD PEST mutations, increasing Notch activity by decreasing Notch degradation by the proteosome.…”
Section: Fbw7 Regulates Notch Stability and Is Mutated In T-allmentioning
confidence: 68%
“…SCF FBW7 -mediated degradation of Notch requires phosphorylation of multiple residues. The first phosphorylation event at S2514 mediates Fbw7 binding, and the second at T2512 is required for polyubiquitination of the protein by SCF FBW7 that results in rapid turnover of N ICD by the proteasome (O'Neil et al, 2007;Thompson et al, 2008). Phosphorylation of Notch at S2514 is mediated by CyclinC:cdk8 after recruitment to the Notch activation complex by Maml (Fryer et al, 2004;O'Neil et al, 2007).…”
Section: Fbw7 Regulates Notch Stability and Is Mutated In T-allmentioning
confidence: 99%
“…[29][30][31][32][33]. Notch activation involves the proteolytic cleavage of the Notch ligand/receptor complex by g-secretase to release the Notch intracellular domain (NICD) that translocates to the nucleus and upregulates expression of a number of different downstream genes (34). Different Notch receptors are preferentially activated in different breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Missense mutations in NRR domain likely destabilize inhibitor state of NRR domain, allowing ligand‐independent Notch activation 90. PEST domain is involved in proteasomal degradation of NOTCH 91, 92, and truncations lacking PEST region likely impair the degradation of NOTCH and augment Notch activation.…”
Section: A Complete View Of Notch1 Mutations Across Sccsmentioning
confidence: 99%